Plan de marketing internacional para el fortalecimiento de la microempresa "Mushuk Yashun" del cantón Otavalo - Ormaza, Estefanía T. (2019)
This work is focused on the analysis of the textile production, of hand-embroidered blouses of the micro-enterprise "Mushuk Yashun" for the implementation of an international marketing plan that allows the strengthening of the microenterprise, for this reason, the present investigation has as aim to carry out a marketing study at a global, national and local level, to later analyze the evolution and the most relevant changes that have taken place around the textile sector in general, focusing at length on the micro-enterprise "Mushuk Yashun", We will see what the main causes that prevent the microenterprise is internationalized, a situational diagnosis was made, which allowed to know the situation in which the microenterprise is and thus to be able to determine the study problem. Once the topic and problem to be investigated was clearly defined, the theoretical framework of the investigation was elaborated, with the description of aspects related to the present study, which support the subject and problem from the theoretical - scientific aspect. The next phase of development of this research was the approach of the methodology to be followed, where the type of research is specified, which, in the first instance, was qualitative and quantitative; then, a collection of information was carried out through field research; by means of investigative methods and techniques that allowed to respond to the proposed objectives and finally the conclusions and recommendations are made based on the results obtained. The research carried out results in the design of an International Marketing plan for hand-embroidered Otavalo blouses that allows the micro-enterprise "Mushuk Yashun" to internationalize one of its most valued products and increase its economic income.